Cellobiose dehydrogenase from Volvariella volvacea and its effect on the saccharification of cellulose. (September 2017) - Chen, Kaixiang; Liu, Xingchen; Long, Liangkun; Ding, Shaojun
Graphical abstract: Highlights: A cellobiose dehydrogenase (VvCDH) from V. volvacea was expressed in Pichia pastoris with its native signal peptide. VvCDH differs from other basidiomycetous CDHs in optimum pH, and discrimination against α-linked disaccharide or monosaccharides. Addition of VvCDH to T. reesei cellulases significantly increased the overall hydrolysis yield of cellulosic substrates. Large amount of gluconic acid was generated along with the hydrolysis of filter paper and delignified wheat straw. Abstract: A gene encoding cellobiose dehydrogenase (VvCDH) from Volvariella volvacea was successfully expressed in Pichia pastoris with codon optimization using its native signal sequence. VvCDH had optimum pH and temperature at 5.5 and 60 °C respectively and showed a broad range of pH stability between 5 and 8. Kinetic analysis showed that the best substrate is cellobiose and that the K m for celloolgosaccharides increases with substrate length. Moreover, lactose is also efficiently oxidized, but glucose and maltose are poor substrates. A large amount of gluconic acid was generated and the overall hydrolysis yield was increased when adding VvCDH to Trichoderma reesei D-86271 enzymatic cocktail during hydrolysis of cellulose substrates, indicating VvCDH involved in the enzymatic cellulose saccharification. VvCDH shows some different enzymatic properties from basidiomycetous CDHs and can be supplemented to T. reesei cellulase cocktail for commercial application.